Nature and nurture, danger and delight: Urban women's experiences of the natural world - KONG, Lily (Institutional Knowledge at Singapore Management University, 1997)
In this paper, we address a research lacuna in the area of human experience of, and interaction with, nature. We focus on women in an urbanized setting, exploring their actual and desired experiences of the natural world, using Singapore as a case study. Our intention is to contribute to both the evolving theoretical and empirical discussions on this subject. Based on data collected from focus group discussions and household questionnaires, we conclude that women's relationships with nature in Singapore are underscored by a strong inclination towards nurturing: teaching, tending and caring, in a way that is not as apparent in men's relationships with nature. Women's relationships with nature may also be conceptualized in terms of ‘danger’ and ‘delight’, a fine balance between ambivalent experiences of fear and enjoyment. In comparing results based on the Singapore context with those in Britain, sources of enjoyment appear to be similar, but the different social situations have resulted in different sources of fear. We conclude by putting forward some recommendations for planning and designing green areas that may enhance women's use and enjoyment of nature areas.